The Influence of Communication of Youth Administrators (Naposo bulung) on the Practice of Christian Youth's Faith Life (Case: HKBP Kobun Kopi Resort Kobun Kopi Church) - Sirait, Tumpal Richardo (Lembaga Riset Mutiara Akbar, 2025)
The purpose of this study is to determine the extent of the influence of Youth Management Communication (Naposobulung) on the practice of Christian Youth Faith in the HKBP Kobun Kopi Resort Kobun Kopi Church. The population of the study was Naposo Bulung (Youth) HKBP Kobun Kopi with a total of 41 people. This study uses a descriptive method while the data analysis used in hypothesis testing is Pearson Product Moment correlation and the data collection tool is a closed questionnaire for variables X and Y. To determine the extent of the influence of Youth Management Communication (naposobulung) on the practice of Christian Youth Faith, the Pearson product-moment correlation statistical test was used. From the test results obtained r = 0.71 while to determine the significance of the correlation coefficient at a real level of 0.05 used the